Evaluación de la corrección angular de la integral velocidad tiempo en ecocardiografía. Estudio piloto - Ugalde C., Diego; Brugere O., Solange; Pino L., Angela (Revista Hospital Clínico Universidad de Chile, 2019)
Background: Echocardiography has now a pivotal role as a tool for hemodynamic monitoring, particularly in the critically ill. However, the ideal acoustic window for relevant measurements such as the velocity time integral are not always available. We propose to evaluate if angular correction of this variable is accurate in comparison with standard technique. Patients and methods: Adult patients were evaluated in the echocardiography unit during Juny 2017, having velocity time integral measured with angulation and standard technique, with convenience sampling. Analysis included difference, means and correlation between basal results and maximal angulation, in Stata 12. Results: 25 patients were included, mean velocity time integral was 23,01cm and with a mean angulation of 32,56º the integral was 24,27cm, with 5,5% difference, statistically significant, linear correlation had a 0,932 coefficient with R-square of 0,7897. Bland-Altman analysis revealed mean difference -1,256cm and agreement limits of -5,219 to 2,707. Discussion: In this study the result of the velocity time integral with angular correction had a good correlation and acceptable precision compared with non-angled measurements, which could allow its use when the acoustic window is sub-optimal, however, these findings should be replicated in critically ill patients.